What Blockchain Are We Talking About? An Analytical Framework for Understanding Blockchain Applications in Agriculture and Food - van Wassenaer, Lan; Verdouw, Cor; Wolfert, Sjaak (Frontiers in Blockchain, 2021)
With the many promises it holds in addressing problems concerning information exchange and digital transactions in multi-actor processes, blockchain technology (BCT) has gained considerable traction in the agrifood sector. Governments, international organisations, private companies, consortia of public and private actors are launching various blockchain projects for improving transparency, traceability, and many other key issues in the agrifood sector. This has resulted in a large number of use cases. It is often unclear, however, what kind of blockchain is applied in different use cases. Due to the novelty and elusiveness of the technology, there is no ready-to-use analytical framework or guideline yet for assessing its applicability and choosing the right technical and organisational setup. As a result, many stakeholders have to grope in the dark when designing and implementing their ‘blockchain application’. Based on studies of use cases worldwide and experiences in organising different blockchain pilots in the Netherlands, this paper seeks to address this problem by providing an overview of the choices to be made at three layers of a blockchain application: the ledger, the governance structure and the ecosystem. This can serve as a reference framework for understanding different blockchain applications and choosing key parameters for new use cases in the agrifood sector. It is expected that such demystification of the blockchain will contribute to more realistic and effective application of the technology to pressing problems in agriculture and food.